2001
DOI: 10.1007/s003820000116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atmosphere-ocean interaction on the interannual variability of winter temperature in Taiwan and East Asia

Abstract: This study investigated the ocean-atmosphere interaction eect on the winter surface air temperature in Taiwan. Temperature ¯uctuations in Taiwan and marine East Asia correlated better with a SST dipole in the western North Paci®c than the SST in the central/ eastern equatorial Paci®c. During the warm (cold) winters, a positive (negative) SST anomaly appears in marine East Asia and a negative (positive) SST anomaly appears in the Philippine Sea. The corresponding lowlevel atmospheric circulation is a cyclonic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…It was also revealed that the establishment of the anomalous SST dipole in the western North Pacific region during DJF and MAM periods is related to an anomalous anti-cyclonic/cyclonic circulation over the southern Philippines and northern Borneo. It is through this regional atmosphere-ocean interaction that the ENSO-precipitation relationship over the southern Philippines and northern Borneo is maintained (Hsu et al, 2001;Wang et al, 2003;Tangang and Juneng, 2004;Juneng and Tangang, 2005); thus modest prediction skills over the region are present during the JFM period. However, as noted earlier, the inclusion of anomalous regional SST in the western North Pacific region did not enhance the model skills.…”
Section: Discussionmentioning
confidence: 99%
“…It was also revealed that the establishment of the anomalous SST dipole in the western North Pacific region during DJF and MAM periods is related to an anomalous anti-cyclonic/cyclonic circulation over the southern Philippines and northern Borneo. It is through this regional atmosphere-ocean interaction that the ENSO-precipitation relationship over the southern Philippines and northern Borneo is maintained (Hsu et al, 2001;Wang et al, 2003;Tangang and Juneng, 2004;Juneng and Tangang, 2005); thus modest prediction skills over the region are present during the JFM period. However, as noted earlier, the inclusion of anomalous regional SST in the western North Pacific region did not enhance the model skills.…”
Section: Discussionmentioning
confidence: 99%
“…The particular circulations affecting northern Taiwan are the negative and positive SLP anomalies in the East Asian coast and the Philippine Sea, respectively. It has been found that the same cyclonic/anti‐cyclonic anomalous flow had a great impact on the East Asian winter and summer monsoon during El Niño years [ Chang et al , 2000a, 2000b; Wang et al , 2000; Hsu et al , 2001]. This anomalous circulation, which can be explained as the Rossby wave response to the SST anomaly in the equatorial Eastern Pacific, once forced can maintain itself for several seasons from winter to summer through local ocean‐atmosphere interactions in the Philippine Sea and the continental shelf region [e.g., Lau and Nath , 2000; Wang et al , 2000; Hsu et al , 2001; Wang and Zhang , 2002; Lau and Nath , 2003; Chou , 2004].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Previous studies showed that the interannual variability of surface THF is associated with the sea ice variability over North Pacific (Liu et al 2007) and the East Asian winter monsoon (Hsu et al 2001). The correlation coefficients of SHF, LHF, and THF with East Asian winter monsoon index, calculated following the method of Jhun and Lee (2004) are 0.74, 0.44, and 0.53, respectively, above a 99% confidence level during 1958/59-2007/08.…”
Section: Wnpo Warmingmentioning
confidence: 81%
“…In addition, Yeh and Kim (2010) and Park et al (2011) have demonstrated that a warming region in the Yellow/East China Sea has been stretched out in a northeast-southwest direction and extends eastward to Japan during the boreal winter, and the warming rate in winter increases up to 3.08C (100 yr) 21 . The increased WNPO releases more heat and moisture to the atmosphere through strong northwesterly winds, with a cold/dry air mass associated with the winter monsoon (Hsu et al 2001). In spite of the aforementioned evidence, there are just a few studies on the relationship between decadal and interannual variability of the SST and atmospheric circulation over the WNPO (Chan and Liu 2004;Peng and Whitaker 1999) and the impact of WNPO warming on the atmospheric response during the boreal winter (Frauenfeld et al 2005).…”
Section: Introductionmentioning
confidence: 99%